1994
DOI: 10.1002/nt.2620020503
|View full text |Cite
|
Sign up to set email alerts
|

Growth and toxin production of the toxic dinoflagellate Pyrodinium bahamense var. compressum in laboratory cultures

Abstract: Toxin production of a Malaysian isolate of the toxic red tide dinoflagellate Pyrodinium bahamense var. compressum was investigated at various stages of the batch culture growth cycle and under growth conditions affected by temperature, salinity, and light intensity variations. In all the experiments conducted, only 5 toxins were ever detected. Neosaxitoxin (NEO) and gonyautoxin V (GTX5) made up 80 mole percent or more of the cellular toxin content and saxitoxin (STX), GTX6 and decarbamoylsaxitoxin (dcSTX) made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
4

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 24 publications
0
54
0
4
Order By: Relevance
“…These temperature tolerances support po tential climate-related range expansion (Usup et al 2012). Although the majority of environmental variables examined influence the PSP toxin profile, not total toxin content, one study demonstrated increased toxicity at low temperature (Usup et al 1994).…”
Section: Temperaturementioning
confidence: 53%
See 1 more Smart Citation
“…These temperature tolerances support po tential climate-related range expansion (Usup et al 2012). Although the majority of environmental variables examined influence the PSP toxin profile, not total toxin content, one study demonstrated increased toxicity at low temperature (Usup et al 1994).…”
Section: Temperaturementioning
confidence: 53%
“…Paz et al (2007) also reported that yessotoxin production decreased with increasing salinity in this species. Toxicity in this species was demonstrated to be relatively unchanged above sal inity 24, but was enhanced 3-fold at salinity 20 (Usup et al 1994). Karenia brevis is thought to tolerate a range of salinities (18−45) but seems to grow best in full-salinity seawater (Magana & Villareal 2006, Brand et al 2012).…”
Section: Salinitymentioning
confidence: 95%
“…This interprctation has to be carefully contrasted with observations of changes and variations in toxin composition in other dinoflagellate species such as Pyrodinium bahamense and Gymnodinium catenatum (Oshima et al 1993;Usup et al 1994). In these organisms, STX has been postulated to be a precursor or parent compound that is rapidly converted into NE0 or GTXS, as these last two compounds are predominant and only negligible amounts of STX are detected (Oshima et al 1993;Usup et al 1994). In an integrated sheme of the STX biosynthetic pathway, interconversions among the toxins would be determined in part by the presence or absence of the appropriate enzymes, but actual toxin production would be the result of the accumulation of only one precursor or parent compound.…”
Section: Discussionmentioning
confidence: 99%
“…The extracts were stored at -20°C before analysis. The extracts were analyzed by HPLC (Oshima et al 1989) incorporating the modifications previously described by Anderson et al (1994).…”
Section: Methodsmentioning
confidence: 99%
“…compressum clone originating from the same site in the Philippines, PBC-MZ-061,593, whose growth rate (k) ranged from 0.2 to 0.3 div d −1 (Gedaria et al 2007). An isolate from Sabah, Malaysia had a faster growth rate (k) of 0.3-0.4 div d −1 (Usup et al 1994). Environmental and possibly genetic factors may explain this variability.…”
Section: Discussionmentioning
confidence: 98%